The Expression Analysis of Complement Component C3 during Early Developmental Stages in Olive Flounder (Paralichthys olivaceus) - Lee, Jang-Wook (Dev Reprod, 2013)
Fish larvae are immediately exposed to microbes from hatching to maturation of their lymphoid organs, therefore effective innate mechanisms is very important for survival in such an environment. The key component of innate immune system, C3 is central protein of all activation pathways of the complement system, leading to inflammatory reactions, such as opsonisation, chemotaxis, and cell lysis of pathogens. Although, innate mechanisms is essential for survival in the early stage of development, little is known about defence mechanisms. In this study, the alignment analysis showed that amino acid sequence of C3 from olive flounder liver EST homologous to other known C3 sequences with 73-99% identity. Also, we examined the tissue distribution of olive flounder C3 and analyzed expression pattern from the fertilized egg until 28 days post hatching. As a result, olive flounder C3 mRNA was expressed only in the liver and the mRNA level more increased as developmental proceed during the early stage. These results may suggest that olive flounder C3 plays an important function in the early immune response of olive flounder larvae.